Metal-Free Ammonium Iodide Catalyzed Oxidative Dehydrocoupling of Silanes with Alcohols - Yuan, Yan-qin; Kumar, Pailla Santhosh; Guo, Sheng-rong (Synlett, 2017)
An ammonium iodide catalyzed direct oxidative coupling of silanes with alcohols to give various alkoxysilane derivatives was discovered. tert-Butyl hydroperoxide proved to be an efficient oxidant for this transformation. Attractive features of this protocol include its transition-metal-free nature and the mild reaction conditions.
Keywords: silylation; ammonium iodide; silanes; alcohols; coupling; metal-free catalysis